2020
DOI: 10.1186/s12981-020-00300-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of AIDS-defining events at initiation of antiretroviral therapy on long-term mortality of HIV/AIDS patients in Southwestern China: a retrospective cohort study

Abstract: Objective: To evaluate the impact of AIDS-defining events (ADE) on long-term mortality of HIV positive individuals on antiretroviral therapy (ART), a retrospective HIV/AIDS treatment cohort study performed in Southwestern China. Methods: The retrospective cohort was conducted among 6757 HIV/AIDS patients on ART (2NRTIs + 1NNRTI, 2NRTIs + 1PI and Single or two drugs) recruited in Guigang city, Guangxi, China, from January 2004 to December 2018. Participants were divided into ADE and non-ADE groups, and were fol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…Since the identification of the first individual infected with HIV in Guangxi in 1996 [ 2 ], the number of infected individuals has increased. By the end of 2017, Guangxi has the second highest number of reported HIV cases (113,500) in the country [ 3 ]. The Free Antiretroviral Treatment Program was launched in 2003 in China, and the “Treat for All” policy was implemented in 2016, and under which HIV-positive individuals were treated after being diagnosis of HIV regardless of their CD4+ cell count [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the identification of the first individual infected with HIV in Guangxi in 1996 [ 2 ], the number of infected individuals has increased. By the end of 2017, Guangxi has the second highest number of reported HIV cases (113,500) in the country [ 3 ]. The Free Antiretroviral Treatment Program was launched in 2003 in China, and the “Treat for All” policy was implemented in 2016, and under which HIV-positive individuals were treated after being diagnosis of HIV regardless of their CD4+ cell count [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, osteoarticular surgery was indicated for up to 43.5% of HIV/AIDS patients with 17 infectious and noninfectious diseases, including ICD-10 codes A18.007 + M49.0*, M87.800 × 051, and S72.000; these codes correspond to Pot’s disease (tuberculosis spondylitis), ischemic necrosis of the femoral head, and femoral fracture, respectively. Epidemiological data from Guangxi indicated that the proportion of HIV/AIDS patients with concurrent extrapulmonary tuberculosis was 8.86% ( Huang et al, 2020 ); meanwhile, AIDS unrelated diseases and fractures also accounted for a large proportion of these orthopedic surgery cases. As a result, the proportion of osteoarticular surgeries is higher in our data.…”
Section: Discussionmentioning
confidence: 99%
“…5 Some of the other factors that are associated with survival outcomes in children on ART are age and gender of the child, type of setting (such as resource rich or resource limited), nutritional status of the child and presence of AIDS-defining illness. [6][7][8][9] Another important factor that needs to be considered is adherence to medications. Adherence in children may depend on the type of Open access regimen, demographic and clinical characteristics of children, and even the knowledge about ART and characteristics of their caregivers.…”
Section: Introductionmentioning
confidence: 99%